Gender differences in computer-mediated communication: the curious case of Millennials in Malaysia - Fung, Kirstie Tet Mei (Universiti Malaysia Sarawak (UNIMAS), 2017)
This study aims to analyse types of communication styles among millennials in Malaysia as well as discovering the reasons for implementing them in social interactions on social media platforms. The platform used in this research was Facebook and millennials were the focus group. A framework based on Herring's (1994) research about observing gender languages on an online academic discussion serves as the basis of this research. This research implements a triangulation method for strengthening the methodology which includes observation, content analysis and semi-structure interviews. Facebook extracted comments from various pages were obtained and analysed with the first two methods whereas semi-structure interviews were carried out with 20 participants. The findings show that not all gender communication style as proposed by Herring (1994) belong to their respective genders and it does show that both genders adopt their counterpart gender's style when interacting. Notable differences in identifying the genders include word choice, sentence structure, topic of discussion, usage of emoticons and usage of hashtags. In conclusion, online interaction still perceives gender language as distinguishable, however, it is uncertain if it will remain the same in the future.